Mikrozonasi Seismik Menggunakan Metode Horizontal to Vertical Spectral Ratio (HVSR), Studi Kasus: Institut Teknologi Sumatera (ITERA) - Rifa Salma Salsabila; Erlangga Ibrahim Fattah; Dian Darisma; Dian Meutia Hidayati; Uswatun Hasanah (Yayasan Literasi Sains Indonesia, 2025)
Institute of Technology Sumatra (ITERA), as an educational institution located in the Lampung Province, continues to strive for the development of educational support facilities such as lecture halls and laboratories. The ITERA campus is in an area with potential natural disaster threats like earthquakes, due to the tectonic activity of the Great Sumatran Fault and the subduction of the Indo-Australian plate and the Eurasian plate. To mitigate the risk of disasters on the ITERA campus, infrastructure development planning requires a seismic microzonation study. This research was conducted to determine the dominant frequency (f0​), amplification factor (A0​), and seismic vulnerability index (Kg​) using the Horizontal to Vertical Spectral Ratio (HVSR) method. The results show that the dominant frequency (f0​) values range from 1 to 4 Hz, the amplification factor (A0) from 1.8 to 4, and the seismic vulnerability index (Kg​) from 2 to 15. The seismic microzonation map of the ITERA campus, the northern part of the area is categorized as having a medium to high seismic vulnerability index (Kg​), with a low dominant frequency (f0​) and a high amplification factor (A0​).